Functional textiles for improved performance, protection and health - Pan, N.; Sun, Gang, 1956- (Woodhead Publishing, 2011)
The textile industry is increasingly based on ongoing innovation and development of higher performance products, and the field of functional textiles is no exception. This book explores the development of textiles with a wide range of functions, with the aim of improving the performance of the product in terms of the protection and health benefits that it can offer. The book is split into two parts. Part one focuses on functional textiles for improved performance and protection, with chapters reviewing antistatic, flame retardant and infrared functional textiles, among many others. Chapters in part two examine the uses of functional textiles in a medical context, including superhydrophobic materials, antibacterial textiles and insect-repellent materials. With its distinguished editors and contributions from some of the world's leading authorities, Functional textiles for improved performance, protection and health is invaluable for textile scientists, technologists and engineers as well as those designing and manufacturing textiles. It is also a suitable reference for the academic sector. Examines the use of functional textiles in a medical context, including superhydrophobic materials, antibacterial textiles and insect-repellent materialsTopics range from textile chemicals and their interaction with skin to novel pesticide protective clothingConsiders anti-ultraviolet protection of clothing and flame retardant textiles.
"The Textile Institute."
Keywords: Smart materials.; Textile fabrics -- Technological innovations.; Biomedical materials.; elektronické knihy; electronic books